EM BUSCA DA LIBERDADE LEGAL: ESCRAVOS E OS AUTOS DE PETIÇÃO DE ANTONINA/PR (1871-1888) - SANTOS, CLEYTON ADRIOVANI DOS (2022)
The objective of this work is to know one of the forms of struggle for freedom in legal ways by slaves from the region of Antonina/PR, between 1871 and 1888. The main source of this research was the Freedom Actions, available at the Centro de Documentation and Memory of the State University of the Midwest, campus of Irati/PR, (CEDOC/I). This documentation is analyzed based on theoretical-methodological proposals that when observing how, in everyday life, tensions develop between strategies, of the masters, and tactics, of the enslaved. We are also guided by the evidentiary methodology, which considers that the work of the historian is similar to that of the researcher/detective and the doctor, for whom small details can mean indications of something relevant. The historiography of slavery in Brazil and Paraná was also consulted. The proposal is to discuss how enslaved men and women sought their manumission by resorting to justice, how freedom actions were elaborated and reflect on how this process occurred in Antonina at the end of the 1800s.